Microarray-based genomic analysis identifies germline and somatic copy number variants and loss of heterozygosity in acute myeloid leukaemia - Ambayya @ Ampiah, A Angeli; Sasmita, Andrew Octavian; Seman, Zainina; Chang, Kian Meng; Sathar, Jameela; Yegappan, Subramanian; Md Noor, Sabariah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Insights into molecular karyotyping using comparative genomic hybridization (CGH) and single nucleotide polymorphism (SNP) arrays enable the identification of copy number variations (CNVs) at a higher resolution and facilitate the detection of copy neutral loss of heterozygosity (CN-LOH) otherwise undetectable by conventional cytogenetics. The applicability of a customised CGH+SNP 180K DNA microarray in the diagnostic evaluation of Acute Myeloid Leukaemia (AML) in comparison with conventional karyotyping was assessed in this study. Methods: Paired tumour and germline post induction (remission sample obtained from the same patient after induction) DNA were used to delineate germline variants in 41 AML samples and compared with the karyotype findings. Results: After comparing the tumour versus germline DNA, a total of 55 imbalances (n 5-10 MB = 21, n 10-20 MB = 8 and n >20 MB = 26) were identified. Gains were most common in chromosome 4 (26.7%) whereas losses were most frequent in chromosome 7 (28.6%) and X (25.0%). CN-LOH was mostly seen in chromosome 4 (75.0%). Comparison between array CGH+SNP and karyotyping revealed 20 cases were in excellent agreement and 13 cases did not concord whereas in 15 cases finding could not be confirmed as no karyotypes available. Conclusion: The use of a combined array CGH+SNP in this study enabled the detection of somatic and germline CNVs and CN-LOHs in AML. Array CGH+SNP accurately determined chromosomal breakpoints compared to conventional cytogenetics in relation to presence of CNVs and CN-LOHs.